Comparison of breastfeeding practice using deuterium oxide dose to mother technique with maternal recall breastfeeding practice among mothers in Klang Valley - Chong, Guey Yong; Nik Shanita Safii,; Noor Zahila Mat Isa,; Norimah A. Karim, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The assessment of exclusive breastfeeding is important to invest the efforts to promote and support breastfeeding practices. Hence this study was carried out to compare breastfeeding practices among mothers using deuterium dose to mother technique with maternal recall breastfeeding practice. A total of 30 mother-infant pairs from a university hospital and government health clinics in Klang Valley participated and completed the study. Mother-infant pairs were recruited into the study when infants were aged 3 months ± 1 week. Anthropometric measurements (height, weight, waist circumference for mother; length and weight for infant) were carried out. Socio-demographic questionnaire was self-administered while breastfeeding practices were interview administered using maternal recall breastfeeding practice questionnaire (MRBF). This was followed by baseline saliva collection of mother-infant pairs before dose and 6 days after mothers were given 30 ± 0.01 g of D2O. The post dose saliva sample of mother-infant pairs were collected 6 times at day 1,2,3,4,13 and 14.The results showed that majority of mothers (57%) were university graduates but majority were stay at home mothers. Meanwhile, mothers had BMI with mean 25 ± 4 kg/m2. The results from MRBF questionnaire showed that all mothers were practicing exclusive breastfeeding and their infant never received any water sources other than their breast milk. However, the deuterium dose to mother technique revealed only 3% of mothers were actually practicing exclusive breastfeeding. From the isotopic data, the calculated mean intake of milk was 721 ± 243 g/day while the mean non-milk oral intake of 122 ± 22 g/ day. In contrast exclusive breastfeeding infants received only 10 g/day non milk oral intake, demonstrating exclusive breastfeeding practice of mothers. There were different breastfeeding practice reported from mother using deuterium oxide dose to mother technique with maternal recall breastfeeding practice.